Muscle MRI in McArdle Disease: A European Multicenter Observational Study. (11th October 2022) - Løkken, Nicoline; Revsbech, Karoline Lolk; Jacobsen, Laura Nørager; Martinuzzi, Andrea; Martin, Miguel Ángel; Díaz-Manera, Jordi; Dominguez-Gonzalez, Cristina; Brondani, Giovanni; Musumeci, Olimpia; Granata, Francesca; Stefan, Cristina; Merino-Sanchez, Concepción; et al.
Abstract : Background and Objectives: Glycogen storage disease type V (GSDV) or McArdle disease is a muscle glycogenosis that classically manifests with exercise intolerance and exercise-induced muscle pain. Muscle weakness and wasting may occur, but it is typically mild and described as located around the shoulder girdle in elderly patients. Paraspinal muscle involvement has received little attention in the literature. This study aimed to quantify fat replacement of paraspinal, shoulder, and lower limb muscles by magnetic resonance imaging in a European cohort of patients with GSDV. Methods: This observational study included patients with verified GSDV and healthy controls (HCs). Whole-body MRIs and clinical data were collected. The degree of muscle fat replacement was evaluated on T1-weighted images with the semiquantitative visual Mercuri scale and on Dixon images where individual muscle fat fractions (FFs) were quantitatively calculated. Results: MRIs and clinical data from a total of 57 patients with GSDV (age 44.3 ± 15.2 years) from 5 European centers were assessed and compared with findings in 30 HCs (age 42.4 ± 14.8 years). Patients with GSDV had significantly more fat replacement of the paraspinal muscles compared with HCs on all levels investigated, detected by both the Mercuri and the Dixon method (Dixon, paraspinal composite FF [GSDV vs HC] at the cervical level: 31.3 ± 13.1 vs 15.4 ± 7.8; thoracic level: 34.5±19.0 vs 16.9±8.6; and lumbar level: 43.9 ± 19.6 vs 21.8 ± 10.2 [ p < 0.0001]). Patients with GSDV also had significantly more fat replacement of the shoulder muscles (evaluated by the Mercuri scale), along with significantly, but numerically less, fat replacement of thigh and calf muscles compared with HC (Dixon, lower limb composite FF [GSDV vs HC] at the thigh level: 12.0 ± 5.6 vs 8.8 ± 2.7 and calf level: 13.1 ± 6.7 vs 9.1 ± 2.9 [ p ≤ 0.05]). Discussion: The primary findings are that patients with GSDV exhibit severe fat replacement of the paraspinal muscles, which can have important implications for the future management of patients with GSDV, and also significant fat replacement of shoulder girdle muscles as previously described. The clinical relevance of the discrete increases in lower limb FF is uncertain. The changes were found to be age-related in both groups, but an accelerated effect was found in GSDV, probably due to continuous muscle damage.